Heterogeneous photocatalytic treatment of organic dyes in air and aqueous media - Rajeshwar, K.; Osugi, M. E.; Chanmanee, W.; Chenthamarakshan, C. R.; Zanoni, Maria Valnice Boldrin [UNESP]; Kajitvichyanukul, P.; Krishnan-Ayer, R. (Elsevier, 2008)
This review focuses on the heterogeneous photocatalytic treatment of organic dyes in air and water. Representative studies spanning approximately three decades are included in this review. These studies have mostly used titanium dioxide (TiO2) as the inorganic semiconductor photocatalyst of choice for decolorizing and decomposing the organic dye to mineralized products. Other semiconductors such as ZnO, CdS, WO3, and Fe2O3 have also been used, albeit to a much smaller extent. The topics covered include historical aspects, dark adsorption of the dye on the semiconductor surface and its role in the subsequent photoreaction, semiconductor preparation details, photoreactor configurations, photooxidation kinetics/mechanisms and comparison with other Advanced Oxidation Processes (e.g., UV/H2O2, ozonation, UV/O3, Fenton and photo-Fenton reactions), visible light-induced dye decomposition by sensitization mechanism, reaction intermediates and toxicity issues, and real-world process scenarios. © 2008 Elsevier B.V. All rights reserved.
Keywords: Electron-hole pairs; Free radicals; Langmuir-Hinshelwood mechanism; Photoexcitation; Solar irradiation; Adsorption; Cadmium compounds; Decomposition; Electric conductivity; Excitons; Free radical reactions; Irradiation; Ozone; Ozone water treatment; Ozonization; Photocatalysis; Photooxidation; Semiconducting cadmium compounds; Semiconductor materials; Solar radiation; Titanium; Titanium dioxide; Wastewater treatment; Water treatment; Zinc oxide; Advanced Oxidation Processes; Aqueous medias; Cds; Dark adsorptions; Fenton reactions; Inorganic semiconductors; Organic dyes; Ozonation; Photocatalytic treatments; Photoreaction; Photoreactor; Reaction intermediates; Real-world process; Semi-conductor surfaces; Sensitization mechanisms; Visible lights; Zno; Semiconducting organic compounds